Design and Implementation of a Mobile-Based Islamic Book Study Information System Using API Architecture and Flutter Framework at Dayah Aqil Al-Farisi - Ahkam, Mizanul Ahkam; Kurniawati; Elfisa; Riska Gianda; Abubakar; Fahmi Sara (LPPM Politeknik Aceh Selatan, 2026)
The development of mobile-based Islamic learning applications has become a solution to support independent study at Dayah Aqil Al-Farisi, especially for santri and community members who are often unable to attend in-person study sessions due to daily activities. This application, built using the Flutter framework and Laravel as the backend, provides digital access to classical Islamic texts (kitab), prayers, Islamic jurisprudence (Fiqh), and the biography of the Prophet Muhammad SAW. The system utilizes an API architecture to enable seamless communication between the mobile app and the server, allowing users to access study materials anytime and anywhere via smartphones. The design and implementation process include requirement analysis, system modeling with Data Flow Diagrams (DFD), UI/UX design, and integration with a MySQL database. The application also features an admin panel for managing content such as kitab, news, prayers, and Fiqh materials. The result is a user-friendly platform that facilitates self-paced learning and helps preserve traditional Islamic education in a modern digital format. This study concludes that the mobile application effectively addresses attendance issues and enhances accessibility to Islamic teachings.